Development and validation of analytical methodology for quality evaluation of Tibolone in capsule pharmaceutical form through UV spectrophotometry - Augusto Cesar Corte; Leticia Lenz Sfair (Drug Analytical Research, 2019)
Tibolone is a drug used as a hormonal repository and is very important due to its characteristic of helping to reduce the symptoms triggered by the hormonal alteration during the climacteric period. Although widely used, the Brazilian Pharmacopoeia does not have any information about this hormone. In the literature, only studies with methodologies using high performance liquid chromatography for drug quantification were found. Thus, this study aimed to develop and validate analytical method using UV spectrophotometry for quality control of Tibolone in capsule pharmaceutical form. The present study followed the validation parameters present in RDC 166/2017 and ICH Q2 (R1), with acetonitrile as solvent and 225 nm as wavelength. Linearity showed a correlation coefficient higher than 0.99, precision presented a mean of 97.81% and accuracy reached a recovery percentage average of 97.18%. It was concluded that the method can be used in the quality control of Tibolone capsules, besides having a low cost and a less complex methodology and easier to perform compared to HPLC.